2021
DOI: 10.3390/microorganisms10010076
|View full text |Cite
|
Sign up to set email alerts
|

New Biocalcifying Marine Bacterial Strains Isolated from Calcareous Deposits and Immediate Surroundings

Abstract: Marine bacterial biomineralisation by CaCO3 precipitation provides natural limestone structures, like beachrocks and stromatolites. Calcareous deposits can also be abiotically formed in seawater at the surface of steel grids under cathodic polarisation. In this work, we showed that this mineral-rich alkaline environment harbours bacteria belonging to different genera able to induce CaCO3 precipitation. We previously isolated 14 biocalcifying marine bacteria from electrochemically formed calcareous deposits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 89 publications
(171 reference statements)
0
5
0
4
Order By: Relevance
“…Due to the high precipitation potential and the extensive range of ureolytic bacteria across various environments, the urease and carbonic anhydrase (CA) based metabolic pathway is the most extensively studied form of MICP 4,55,56 . The ubiquity and relatively low complexity of the urease/CA metabolism has made it the model process for recent MICP studies on cathodically protected surfaces 3,4,57 . However, a recent study found that marine bacterial strains isolated from cathodically protected surfaces that tested positive for CA and negative for urease production was still able to undergo MICP in the absence of urea 3 .…”
Section: Bacterial Carbonate Biomineralizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the high precipitation potential and the extensive range of ureolytic bacteria across various environments, the urease and carbonic anhydrase (CA) based metabolic pathway is the most extensively studied form of MICP 4,55,56 . The ubiquity and relatively low complexity of the urease/CA metabolism has made it the model process for recent MICP studies on cathodically protected surfaces 3,4,57 . However, a recent study found that marine bacterial strains isolated from cathodically protected surfaces that tested positive for CA and negative for urease production was still able to undergo MICP in the absence of urea 3 .…”
Section: Bacterial Carbonate Biomineralizationmentioning
confidence: 99%
“…The ubiquity and relatively low complexity of the urease/CA metabolism has made it the model process for recent MICP studies on cathodically protected surfaces 3,4,57 . However, a recent study found that marine bacterial strains isolated from cathodically protected surfaces that tested positive for CA and negative for urease production was still able to undergo MICP in the absence of urea 3 . This suggests CA may be critical in other MICP pathways, and that there is a need to expand past urease hydrolysis as the model for MICP, particularly in studies on subsea fouling.…”
Section: Bacterial Carbonate Biomineralizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Par exemple, la calcite a été observée sous forme de sphère, de chou-fleur et d'haltère dans de nombreuses expériences de laboratoire en présence de différentes bactéries (Fig. 2) [1] dont certaines d'origine marine [31,61].…”
Section: Biocalcification Bactérienne Biologiquement Induiteunclassified